Phase-controlled solvothermal syntheses and oxygen evolution reaction (OER) activity of nickel sulfide nanoparticles obtained from 1, 2-bis(diphenylphosphino)ethane nickel(ii) acetylacetonatedithiolate. (16th May 2022) - Singh, Ayushi; Singh, Amita; Kociok-Köhn, Gabriele; Chauhan, Ratna; Gosavi, Suresh W.; Singh, Anar; Singh, Ashish Kumar; Kumar, Abhinav; Muddassir, Mohd.
Abstract : New heteroleptic Ni(ii )dppe dithiolate synthesized and used as a single source precursor for nickel sulfides utilized as electrocatalyst for OER. Abstract : A new heteroleptic nickel(ii ) complex, [Ni(dppe)(acac)]·CHCl3 (1 ) (where acac = acetylacetonatedithiolate, dppe = 1, 2-bis(diphenylphosphino)ethane), has been synthesized and characterized using different spectroscopic techniques and single-crystal X-ray diffraction. The solvothermal decomposition of the complex in two different solvents, viz. 1-dodecanethiol (DT) and octadecyl amine (ODA), yielded two different nickel sulfides, viz. Ni-DT and Ni-ODA, respectively. These sulfides have been characterized by PXRD and SEM. Rietveld refinement analyses of Ni-DT revealed that it comprises two phases of nickel sulfide, viz. NiS and Ni3 S3, while Ni-ODA possesses only a single phase of Ni2 S3 . The newly synthesized materials have been used as electrocatalysts for the oxygen evolution half-cell reaction of water splitting. The electrochemical studies suggest that Ni-DT /Ni-ODA has a good electrocatalytic activity towards the OER at a low overpotential of ∼200 mV with η 1 being 342 mV and 243 mV for Ni-DT and Ni-ODA, respectively, at a scan rate of 1 mV s −1 .